Penyususnan Tes Membaca (Detailliertes Lesen) Tingkat A1 GER Berbasis HOTS - Siti Kudriyah (Universitas Negeri Medan, 2021)
ABSTRACTThe HOTS concept implemented by the government for teaching in schools is closely related to literacy. Literacy here includes the ability to grasp, understand, interpret, and appropriate information/content through various activities, such as attentive reading, seeing, listening, writing, talking and through discussions.More broadly it includes thinking skills using printed, visual, digital, and auditory sources of knowledge. Ideally, the HOTS concept is to be implemented both in all aspects of educational activities within the school and in extra-curricular activities. German classes in the school system as well as within university level in Indonesia are in accordance with international, in this context,European standards (GeR / Gemeinsamer europäischen Referenzrahmen, A1, A2, B1, B2, C1 and C2 levels) of evaluation. The GER standard evaluation has now implemented the HOTS concept. Currently, evaluations within the school system are required to comply with the HOTS concept. Taking the evaluation of reading abilities, the HOTS concept puts emphasis on advancing the ability to think about, differentiate and take up fact-based information and to strengthen creative thinking and the development of ideas. Learners are required to think logically and creatively. In this article, we will discuss reading skills according to the GER reference for level A1, as a standardized test for high school learners. Keywords: HOTS, evaluation, GER reading skill.